Can Anogenital Distance be Used to Select Oocyte Donors with Greater Embryo Production? - A. F. Machado; S. E. Guimarães; D. Lollobrigida Netto; T. Araújo; V. A.P. Alfradique; J. D. Guimarães; V. E. Gomez-Leon (Kansas Agricultural Experiment Station Research Reports, 2025)
In vitro embryo production has increased over the last years as a tool to obtain genetically superior animals. Anti-Müllerian hormone (AMH) concentration and antral follicle count are phenotypes associated with in vitro embryo production but are less accessible at the farm level. Anogenital distance (length from the center of the anus to the base of the clitoris) has been proposed as a new proxy for fertility in dairy cattle that can be collected easily and at a low cost. Bos indicus dairy cattle oocyte donors of the Gyr breed (n = 552) from six herds in Brazil were used to test the association of the historical in vitro embryo production record with anogenital distance and AMH. The historical record of embryo production was retrieved from the farms, and anogenital distance and blood samples to evaluate the concentration of AMH were collected in 2021. Donors were classified as High or Low AMH, High or Low recovered oocytes, and Short or Long anogenital distance categories. Donors in the High AMH and oocyte categories produced more viable oocytes and embryos than donors in the Low AMH and oocyte categories. However, no differences were observed between Short vs. Long anogenital distance for AMH concentration and in vitro embryo production. A limitation of our study was the use of oocyte and embryo data collected retrospectively in relation to the current anogenital distance of the animal. Thus, further studies should be performed to validate these results and to better understand the association between anogenital distance and in vitro embryo production.
Keywords: anogenital distance; anti-Müllerian hormone; in vitro embryo production